HUBUNGAN EKOLOGIS ANTARA MANGROVE DAN KEPITING PADA HUTAN MANGROVE DI DESA KETAPANG INDAH KECAMATAN SINGKIL UTARA KABUPATEN ACEH SINGKIL - Syam’un, Syam’un; Munandar, Munandar; Wintah, Wintah; Hasanah, Uswatun; Muktaridha, Muktaridha (Universitas Mataram, 2025)
Mangrove forests are one of the important ecosystems in coastal areas. The existence of mangrove crabs is greatly affected by the condition of the surrounding mangrove ecosystem. The objectives of the study were to (1) analyze the level of mangrove and crab diversity; (2) analyze mangrove and crab density; (3) analyze the distribution pattern of mangrove and crab communities; (4) analyze the ecological relationship between mangroves and crabs. Mangrove sampling research method with purposive sampling method. Mangrove crab sampling using random sampling method. The results of the study showed that mangrove diversity found 4 species namely; Avicennia marina, Rhizophora mucronata, Rhizophora apiculata, and Sonneratia alba, crab diversity there are 3 species namely; Scylla serrata, Scylla olivacea, and Scylla paramamosin. Mangrove density was relatively high and ranging from 4000-4466,67 ind/ha and crab density ranging from 3,00-3,67 ind/m2. The distribution of mangroves and crabs as a whole has a uniform distribution. Environmental factors that have the most influence on crab density are temperature and substrate factors. The temperature at the study site ranged from 28,47-28,77°C and the substrate at the study site was clay or sandy clay.